The ticks (Acari: Ixodida: Argasidae, Ixodidae) of Bolivia - Mastropaolo, Mariano; Beltrán-Saavedra, L. Fabián; Guglielmone, Alberto (2018)
The tick species reported in Bolivia are reviewed here as (1) endemic or established: Ornithodoros echimys, O. guaporensis, O. hasei, O. kohlsi, O. mimon, O. peropteryx, O. rostratus, Otobius megnini, Amblyomma auricularium, A. cajennense, A. calcaratum, A. coelebs, A. dubitatum, A. humerale, A. incisum, A. longirostre, A. naponense, A. nodosum, A. oblongoguttatum, A. ovale, A. parvitarsum, A. parvum, A. pecarium, A. pseudoconcolor, A. rotundatum, A. scalpturatum, A. tigrinum, A. triste, Dermacentor nitens, Haemaphysalis juxtakochi, H. leporispalustris, I. boliviensis, I. cooleyi, I. luciae, Rhipicephalus microplus, R. sanguineus, and (2) erroneously reported: Ornithodoros puertoricensis, O. talaje, O. turicata, Amblyomma americanum, A. maculatum, A. multipunctum, Ixodes ricinus, I. scapularis, Rhipicephalus annulatus. Many of these records are lacking locality and/or host, and some of them need new findings for confirmation. Some of the species recorded may represent a threat for human and animal health, therefore would be of great value to make a countrywide survey of ticks in order to update the information presented in this work.